Guarding The Elections Online: New Practices, Trust, and Empowerment of Citizens Identities - Antony Lee (Journal of Indonesian Social Sciences and Humanities, 2018)
This paper scrutinizes two relatively similar cyber activisms in Indonesia, namely Guard the 2014 General Election and Guard the 2015 Local Election. The two movements serve as cases to study cyber activisms contributions to democracy. Guard the General Election, which received massive support from the internet users, has been acknowledged as a success story of a cyber political crowdsourcing in Indonesia. Guard the Local Election tried to repeat the success a year after, but received fewer supports. By scrutinizing those movements, this writing attempts to answer two connected questions of (1) how can cyber social movements contribute to democracy? (2) Why were some cyber movements received more popular support than the others? This paper argues, these movements have contributed to democratization in the way that the activisms reshaped civic culture; introducing new practices, empowering citizens identities, and strengthening trust. Also, the writing explores arguments that political momentum and mainstream media coverage are influential on determining the successfulness of cyber movements. Methodologically, this paper subscribes to qualitative content analysis as a tool to examine interviews materials as well as online and offline texts.